Conductive loss of hearing - Subba Rao PS; Syed Mahaboob (Journal of All India Institute of Speech and Hearing, 1970)
The present study is focused on the  conductive loss of hearing observed for the period August 1965 to July 1968 at the A.I.I.S.H., Mysore.   The different aetiological factors are discussed.